MANAGEMENT OF WILT DISEASE OF CUMIN CAUSED BY F. OXYSPORUM F. SP. CUMINI WITH FUNGICIDES IN VITRO AND IN VIVO - DAMA RAM and ANAND CHOUDHARY, HITENDRA JANGIR (The Journal of Research, PJTSAU, 2023)
Cumin is an important seed spice crop. It is affected by several diseases among them wilt disease caused by Fusarium oxysporum is one of the most important and destructive disease causing heavy losses in the crop production. The present study was conducted at College of Agriculture, Jodhpur during Rabi season 2020-21to evaluate the five different fungicides under in vivoand seven different fungicides under in vitro condition. Lowest disease per cent was recorded in carbendazim (50% WP) (12.39%)followed by carbendazim 12% + mancozeb 63% (14.75 %), thiophanate methyl (70% WP) (20.39%) which was at par with tebuconazole 50% + trifloxystrobin 25% WG (75 WG) (20.45%) when tested under in vivo condition. The maximum per cent disease incidence was observed in pyraclostrobin 5% + metiram 55% WG (22.49 %) whereas, 63.59 per cent disease incidence was recorded in control plot. Result of in vitro study indicated that the fungicide carbendazim (50% WP) completely inhibited the mycelial growth of F. oxysporum and also found significantly superior over the other fungicides followed by carbendazim 12% +mancozeb 63% (96.80%), tebuconazole 50% + trifloxystrobin 25% WG (75 WG).